2012
DOI: 10.1097/wnf.0b013e31827453fa
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Duloxetine for the Treatment of Chronic Nonorganic Orofacial Pain

Abstract: Duloxetine significantly relieved chronic nonorganic orofacial pain. Its pain-relieving effect appeared from 2 weeks of treatment. Furthermore, the pain-relieving effects of duloxetine similarly appeared regardless of the presence or absence of baseline depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 26 publications
6
44
0
Order By: Relevance
“…Duloxetine is a selective serotonin (5-HT) and norepinephrine (NE) reuptake inhibitor [40]. Duloxetine has been reported to be effective in diabetic neuropathic pain and recently in chronic orofacial pain disorders, such as burning mouth syndrome [41,42], suggesting other mechanisms of action. Indeed, duloxetine has been shown to act on certain sodium channels, blocking persistent late Nav1.7 currents.…”
Section: Discussionmentioning
confidence: 99%
“…Duloxetine is a selective serotonin (5-HT) and norepinephrine (NE) reuptake inhibitor [40]. Duloxetine has been reported to be effective in diabetic neuropathic pain and recently in chronic orofacial pain disorders, such as burning mouth syndrome [41,42], suggesting other mechanisms of action. Indeed, duloxetine has been shown to act on certain sodium channels, blocking persistent late Nav1.7 currents.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, BMS/AO are relatively common conditions that are often treatment resistant, and new and effective therapeutics are urgently needed. We previously reported that the antidepressant, duloxetine, had some effect on chronic pain around the orofacial region (Nagashima et al, ) but that this effect was not related to its plasma concentration (Kobayashi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Widely used chiral drugs, such as rosuvastatin, duloxetine and salbutamol, play an important role in treating human diseases 1,2,3 . In the environment of living systems, specific binding between molecules ( eg , enzymes, receptors, transporters, and DNA) is required for their medicinal effect.…”
Section: Introductionmentioning
confidence: 99%